EKSTRAKSI FOSFOR DARI LIMBAH BUAH JENGKOL DAN PETAI UNTUK PEMBUATAN PUPUK ORGANIK CAIR - Rentdo Reinnoki; Waskito Rohim; Slamet Priyanto (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Waste jengkol and petai is a class of organic waste that can pollute the environment. For that pollution problemscan be overcome by utilizing the waste into liquid organic fertilizer which can raise the economic value that arebeneficial to the environment. The process of making is solid liquid extraction (leaching) with leaching timevariation, species composition and bioactivator waste type. The mixture is fermented for 25 days once every 5 daysof leachate were taken to measure the content of phosphor. Variation time of leaching showed that the longer time,more and more content of phosphorus is produced. Optimum time on the day to 25 where each variable is theamount of phosphorus in every 663.33 mg / l; 596.69 mg / l; 427.48 mg / l and 398.98 mg / l. Bioactivator type andtype of waste that is used also affects the amount of phosphorus produced. Rendement produced on the 25th dayfrom each variable is 62.07%, 48.28%, 44.83% and 37.93%. The rank of variable composition that produces a highphosphorus content and high yield is jengkol EM4, petai EM4, jengkol Boisca boisca and petai Boisca.